Upaya Meningkatkan Kompetensi Guru dalam Melaksanakan Penilaian Kurikulum 2013 melalui Bimbingan Terstruktur di MIN 2 Gunungkidul - Susiyati Susiyati (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2018)
This research aims to improve the ability of teachers as an effort in carrying out the assessment based on the curriculum at MIN 2 Gunungkidul through structured guidance. The subject of research is the teachers of Gunungkidul MIN 2 years of 2017/2018 Lesson 8 persons consist of 2 teachers are male and 6 female teachers. The research was conducted in three cycles. Research data obtained through observation assessment administration and observation classes. Assessment based on the curriculum on 2013 cycle I the ability of teachers in mastering techniques scoring average value of 74.56. In cycle II, the ability of a teacher in mastering techniques scoring average 84.5. Cycle III the ability of teachers in mastering techniques scoring average value of 87.53. Of the observations obtained improvement belongs to the criteria either. This means that with structured guidance method can be used to improve the ability of teachers in carrying out an assessment based on the curriculum 2013 at MIN 2 Gunungkidul.